The Roles Relevance Development of English Lecturer toward Harmer’s Teaching Theory in Industry Revolution 5.0 (Conference on English Language Teaching, 2023)
This research is the mixed method and aims to determine the relevance of the role of lecturers based on Hammer's theory of classroom teaching during the 5.0 industrial revolution era. The populations of this research were English lecturers who taught at the Tarbiyah faculty in the English study program and the Syariah faculty at Fatmawati Sukarno Bengkulu State Islamic University. Totaling 26 people, the sample used in this study using total sampling technique. Quantitative data is in the form of a Questionnaire which was compiled based on the theory of Harmer, J (1983). The instrument has been tested to obtain validity, reliability,Likert scale, Croncbach Alpha, and “t” test. Qualitative data in the form of analysis based on Hubberman and Miles namely, reduction, display and conclusion verification. The sample interview used purposive sampling, so the numbers of lecturers interviewed were 13 people. The results of the research showed that almost all roles were used by lecturers to teach in class, but the roles that were mostly used by lecturers are Lecturers as an Instructor reaching 90.67%, Lecturers as controller reaching 87.25%, Lecturers as a participant reaching 84.5%, and Lecturers as resources reached 82.5%... The role of lecturers in learning English based on Harmer theory during the industrial revolution 5.0 was still relevant to be applied. This was proven from the score obtained from the interview results, it was obtained that it reached 0.76, meaning that based on the value of the provisions of the Guttmann scale 0.51- 0.75, the association is quite strong (high enough). Based on the data obtained, it showed in fact and rationally that Hammer's theory of teaching is still relevant enough to be applied in the era of the industrial revolution 5.0.